Disc cloaking: Establishing a lower limit to the number density of local compact massive spheroids/bulges and the potential fate of some high-z red nuggets. Issue 3 (29th April 2022) - Hon, Dexter S-H; Graham, Alister W; Davis, Benjamin L; Marconi, Alessandro
ABSTRACT: The near-absence of compact massive quiescent galaxies in the local Universe implies a size evolution since z ∼ 2.5. It is often theorized that such 'red nuggets' have evolved into today's elliptical (E) galaxies via an E-to-E transformation. We examine an alternative scenario in which a red nugget develops a rotational disc through mergers and accretion, say, at 1 ≲ z ≲ 2, thereby cloaking the nugget as the extant bulge/spheroid component of a larger, now old, galaxy. We have performed detailed, physically motivated, multicomponent decompositions of a volume-limited sample of 103 massive (M_*/M_ 1× 10^11 ) galaxies within 110 Mpc. Many less massive nearby galaxies are known to be 'fast-rotators' with discs. Among our 28 galaxies with existing elliptical classifications, we found that 18 have large-scale discs, and two have intermediate-scale discs, and are reclassified here as lenticulars (S0) and elliculars (ES). The local spheroid stellar mass function, size–mass diagram and bulge-to-total ( B / T ) flux ratio are presented. We report lower limits for the volume number density of compact massive spheroids, n c, Sph ∼ (0.17–1.2) × 10^-4 Mpc^-3, based on different definitions of 'red nuggets' in the literature. Similar number densities of local compact massive bulges were reported by de la Rosa et al. using automated two-component decompositions and their existence is now abundantly clear with our multicomponent decompositions. We find disc-cloaking to be a salient alternative for galaxy evolution. In particular, instead of an E-to-E process, disc growth is the dominant evolutionary pathway for at least low-mass (1× 10^10M_*/M_ 4 × 10^10 ) red nuggets, while our current lower limits are within an alluring factor of a few of the peak abundance of high-mass red nuggets at 1 ≲ z ≲ 2.